Circ_0001588 Induces the Malignant Progression of Hepatocellular Carcinoma by Modulating miR-874/CDK4 Signaling. (20th October 2021) - Bin, Xiaoyun; Chen, Yichen; Ma, Jiasheng; Tang, Renchao; Zhao, Zhenrong; Wang, Kangxuan; Wang, Jianchu
Abstract : Accumulating evidence indicates that circular RNAs (circRNAs) can interact with microRNAs to modulate gene expression in various cancers, including hepatocellular carcinoma (HCC). Although the significant role of circRNAs has been well documented in HCC, the complex mechanisms of circRNAs still need to be elucidated. Our current study is aimed at investigating the function of circ_0001588 in HCC, which was observed to significantly increase in HCC tissues and cells. We demonstrated that the knockdown of circ_0001588 resulted in repressed cell proliferation, migration, and invasion. In vivo studies using a nude mouse model showed that circ_0001588 downregulation reduced tumor size. Moreover, miR-874 was predicted as a target of circ_0001588. Using luciferase binding assays, we proved that circ_0001588 functions as a molecular ceRNA of miR-874 and that CDK4 acts as a downstream target of miR-874 in HCC. It was confirmed that overexpression of miR-874 decreased the proliferation, migration, and invasion triggered by the increase in circ_0001588. In summary, our results indicate that circ_0001588 acts as a ceRNA and promotes HCC progression by targeting the miR-874/CDK4 signaling pathway. Hence, we propose that circ_0001588 may be a promising target for HCC treatment.